Gouverner l’Orient romain des tétrarques aux Théodosiens - Sylvain Destephen (Pallas, 2023)
The Roman Empire in the East successfully overcame the political crisis of the last centuries of Antiquity, whilst the western part disappeared after the fifth century. Was the surprising divergence in fate between the two halves of the Roman world due to differences in administrative and military structures? At first sight, these structures were identical, yet they led to radically opposite results. The period between the end of the third century and the beginning of the fifth saw the establishment of a more powerful administration and army, which remained under the close control of imperial power, which also relied upon a dense network of cities. The strength of the hierarchical relationships between emperors, civil servants, soldiers and municipal notabilities largely explains not only the survival but also the dynamism of the Roman Empire in the East during Late Antiquity and beyond.